Problem-Posing Learning Method for Enhancing the Competence of Digital Marketing Students - Astri Wulandari; Dandy Marcelino (Universitas Negeri Malang, 2022)
Adopting a new lecture style will enable students to have meaningful learning and actively interact and solve problems. This study attempts to discover the online marketing professional ethics learning process through the problem-posing method. In doing so, this research involved classroom action research, which is provided through four stages: planning, implementation, observation, and reflection. Through the problem-posing method, lecturers can find solutions to problem-solving for the low scores of these students. Based on the implementation of classroom action research in the first and second cycles, it can be seen that the students’ scores are satisfying, which is indicated by the increase in student scores from pre-test to post-test. This implies that the problem-posing method has successfully enhanced students’ competence in the marketing profession ethics course. Meanwhile, based on the non-test observation sheet, it shows that the students’ response to the implementation of the marketing professional ethics course using the problem-posing method in the first and second cycles is good, but there need to be improvements to obtain a better assessment in the future. Keywords: Problem posing method, learning methods, classroom action research.